The Brighton Collaboration standardized template for collection of key information for benefit-risk assessment of nucleic acid (RNA and DNA) vaccines. Issue 34 (22nd July 2020) - Kim, Denny; Robertson, James S.; Excler, Jean-Louis; Condit, Richard C.; Fast, Patricia E.; Gurwith, Marc; Pavlakis, George; Monath, Thomas P.; Smith, Jonathan; Wood, David; Smith, Emily R.; Chen, Robert T.; et al.
Abstract: Nucleic acid (DNA and RNA) vaccines are among the most advanced vaccines for COVID-19 under development. The Brighton Collaboration Viral Vector Vaccines Safety Working Group (V3SWG) has prepared a standardized template to describe the key considerations for the benefit-risk assessment of nucleic acid vaccines. This will facilitate the assessment by key stakeholders of potential safety issues and understanding of overall benefit-risk. The structured assessment provided by the template can also help improve communication and public acceptance of licensed nucleic acid vaccines.